2022
DOI: 10.3390/jcm11236904
|View full text |Cite
|
Sign up to set email alerts
|

Free Light Chains, High Mobility Group Box 1, and Mortality in Hemodialysis Patients

Abstract: Background: Uremic toxins are associated with immune dysfunction and inflammation. The inadequate removal by hemodialysis (HD) of serum free light chains (FLCs) determines their accumulation. This study evaluated FLCs in HD patients, analyzing their relations with other biomarkers, such as serum high mobility group box 1 (HMGB1). Methods: FLC and HMGB1 were evaluated in a cohort of 119 HD patients. κFLC and λFLC were summated to give a combined (c) FLC concentration. Patients were followed prospectively until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Additionally, ischemia-reperfusion injury is a common cause of AKI, and experimental studies suggest that sex hormones are involved in the regulation of cellular pathways of this injury and may therefore contribute to AKI susceptibility [ 26 , 32 , 33 ]. Furthermore, recently investigated biomarkers of mortality, such as free light chains (FLCs) or serum high mobility group box 1 (HMGB1), may serve as important parameters that reflect inflammation and immune dysfunction in CKD and AKI patients [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ischemia-reperfusion injury is a common cause of AKI, and experimental studies suggest that sex hormones are involved in the regulation of cellular pathways of this injury and may therefore contribute to AKI susceptibility [ 26 , 32 , 33 ]. Furthermore, recently investigated biomarkers of mortality, such as free light chains (FLCs) or serum high mobility group box 1 (HMGB1), may serve as important parameters that reflect inflammation and immune dysfunction in CKD and AKI patients [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hormonal changes resulting from comorbidities such as diabetes contribute to the loss of lean body mass [ 48 ]. The process of PEW is both complex and dynamic, requiring multiple strategies of nutritional, medical and lifestyle intervention [ 10 , 45–47 ]. As improvements in dialysis treatment (such as improved filtration and biocompatibility of medical materials) continue to evolve, dynamic methods to assess their application are increasingly appropriate [ 44–47 ] For providers to accurately assess REE, and its changes over time would provide a powerful tool in monitoring the ongoing need and effectiveness of such interventional strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Both impairment and activation pathways are shown to be involved in immune natural cells in hemodialysis (HD) patients that also have active infections. These studies reported a need for a discrete method for measuring adaptive immune system dysregulation and identifying a distinct inflammatory endotype that reflects reduced defense mechanisms such as phagocytic capabilities or the impairment of the antigen presentation function [ 43 , 44 ]. This distinct immune dysfunction profile was observed in our cohort of patients who were critically ill with severe COVID-19: when compared to the sepsis and septic shock patients, the patients with COVID-19 demonstrated a weakened CD4 T cell response and a reduction in the naïve cell response after CRRT.…”
Section: Methodsmentioning
confidence: 99%